Conformational isomerization: A novel mechanism to realize the AIE‐TADF behaviors. Issue 1 (4th June 2022) - Wu, Hao; Fan, Xiao‐Chun; Wang, Hui; Huang, Feng; Xiong, Xin; Shi, Yi‐Zhong; Wang, Kai; Yu, Jia; Zhang, Xiao‐Hong
Abstract: Thermally activated delayed fluorescence (TADF) materials with aggregation‐induced emission (AIE) features can overcome aggregation‐caused quenching (ACQ) and emit intensely in aggregate states and thus have attracted enormous attention in the fields of high‐efficiency organic light‐emitting diodes, bioimaging, photodynamic therapy, photocatalysis, etc. However, their corresponding exact working mechanisms at the microscopic level are still far from clear. Herein, by carefully investigating the physical properties of our newly designed TADF material 6‐(10H‐spiro[acridine‐9, 9′‐fluoren]‐10‐yl)nicotinonitrile in various states, we concluded that conformational isomerization plays an important role in realizing high photoluminescence quantum yields in its amorphous neat film state, in which the high‐lying quasi‐axial conformations with non‐TADF features and low‐lying quasi‐equal conformations with TADF characteristics serve as the host matrix and dopant, respectively, thus suppressing ACQ in disordered aggregate states. Our work not only offers a new possible microscopic mechanism by using conformational isomerization for the AIE‐TADF phenomenon but also provides a novel method for designing high‐efficiency AIE‐TADF emitters. Abstract : Due to conformational isomerization, the emitter exhibits unique AIE‐TADF behavior. This is mainly because the QA conformers act as a host matrix to dilute TADF QE conformations in neat films, thereby suppressing ACQ and achieving high PLQY. This work proposes a new mechanism to understand the AIE‐TADF behaviors and provides a new idea for extending the design of AIE‐TADF materials.